Decreased duration of intravenous cephalosporins in intensive care unit patients with selective digestive decontamination: a retrospective before-and-after study - Mathieu, Calypso (Eur J Clin Microbiol Infect Dis, 2020)
Selective digestive decontamination (SDD) reduces the rate of infection and improves the outcomes of patients admitted to an intensive care unit (ICU). A risk associated with its use is the development of multi-drug-resistant organisms. We hypothesized that a 1-day reduction in systemic antimicrobial exposure in the SDD regimen would not affect the outcomes of our patients. In this before-and-after study design, 199 patients and 248 patients were included in a 3-day SDD group and a 2-day SDD group, respectively. The rates of hospital-acquired pneumonia and ICU infections were similar in both groups. The rates of bloodstream infection and bacteriuria were significantly lower in the 2-day SDD group than in the 3-day SDD group. Compared with the patients in the 3-day group, the patients in the 2-day SDD group received fewer antibiotics and less exposure to mechanical ventilation, and they used fewer ICU resources. The rates of ICU mortality and 28-day mortality were similar in both groups. The incidence of multi-drug-resistant organisms was similar in both groups. Within the limitations inherent to our study design, reducing the exposure of prophylactic systemic antibiotics in the SDD setting from 3 days to 2 days was not associated with impaired outcomes. Future randomized controlled trials should be conducted to test this hypothesis and investigate the effects on the development of multi-drug resistant organisms. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1007/s10096-020-03966-w) contains supplementary material, which is available to authorized users.